Peningkatan Daya Saing UMKM Kelurahan Sri Menanti Melalui Fasilitasi Perolehan Perizinan Dasar - Occa Roanisca; Robby Gus Mahardika; Maya Yusnita (Universitas Mathla'ul Anwar Banten, 2022)
IMPROVING THE COMVETITVENESS OF UMKM IN SRI MENANTI VILLAGE THROUGH FACILITATING THE ACQUISITION OF PRODUCT LEGALITY. Micro, Small and Medium Enterprises (UMKM) have a very strategic role in the people-based economic development in Indonesia. The strengthening of this role must be increased by equipping businesses with permits that have been determined by the Government, such as food safety education certificates, sanitation hygene-worthy certificates, and home industry food production certificates. There are still many UMKM in Sri Menanti Village that do not have these product legality. Therefore, this service activity will facilitate the management of these permits. The method in this service activity is in the form of direct assistance for submissions, facilitation of laboratory testing costs so that all fostered partners obtain these permits. The fostered partners in this activity amounted to seven UMKM determined by the Sri Menanti Village Party. The result of this service activity is that the seven assisted UMKM managed to get these permits. The seven UMKM already have food safety education certificates, two UMKM have received HS-worthy certificates and five other UMKM have received PIRT certificates. Obtaining this license will make it easier for the assisted UMKM to market their products more broadly.